2022
DOI: 10.1167/iovs.63.5.3
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical Reverse Correlation Revealed Broader Orientation Tuning and Prolonged Reaction Time in Amblyopia

Abstract: Purpose Neural selectivity of orientation is a fundamental property of visual system. We aim to investigate whether and how the orientation selectivity changes in amblyopia. Methods Seventeen patients with amblyopia (27.1 ± 7.1 years) and 18 healthy participants (25.1 ± 2.7 years) took part in this study. They were asked to continuously detect vertical gratings embedded in a stream of randomly oriented gratings. Using a technique of subspace reverse correlation, the ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 92 publications
(114 reference statements)
1
5
0
Order By: Relevance
“… 59 , 60 Given that Ter s in both AE and FE were found to be increased, we speculate that the prolonged Ter is more likely reflecting the deficits in the post-sensory processes that are outside V1 in amblyopia. Our speculation agrees with the result from other amblyopia studies in manual response time 61 and in saccadic delay. 21 , 62 People have also suggested that amblyopia impaired attention 12 , 63 and may impact cortical connections to higher brain areas, including parietal and frontal cortices.…”
Section: Discussionsupporting
confidence: 93%
“… 59 , 60 Given that Ter s in both AE and FE were found to be increased, we speculate that the prolonged Ter is more likely reflecting the deficits in the post-sensory processes that are outside V1 in amblyopia. Our speculation agrees with the result from other amblyopia studies in manual response time 61 and in saccadic delay. 21 , 62 People have also suggested that amblyopia impaired attention 12 , 63 and may impact cortical connections to higher brain areas, including parietal and frontal cortices.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, the continuous tracking paradigm has a long stream of dynamic stimuli with simultaneous response collection and thus is capable of collecting multiple responses within a second. 24 27 , 33 , 50 It has been shown that the continuous tracking paradigm can provide the psychophysical measure equivalent to that in a conventional trial-based paradigm 24 , 26 with similar precision but in a shorter time (120 tracking trials vs. 4860 discrete trials). 24 In addition, the continuous tracking task is more natural compared to the repetitive conventional trials because our daily visual tasks such as driving or looking for a familiar face in the crowded street are rarely discrete.…”
Section: Discussionmentioning
confidence: 99%
“…The high-throughput stimulus–response data series generated by the continuous tracking paradigm allowed us to apply cross-correlation to study human tracking in a more rigorous manner. 24 , 25 , 33 , 53 Cross-correlation has been widely used in the analysis of neural data to reveal the neuron receptive fields in physiology. 28 , 30 32 It has also been employed to uncover the spatiotemporal weighting functions of sensory processes in psychophysics, such as orientation tuning, 33 , 54 disparity tuning, 55 perceptual template, 56 , 57 eye movement, 50 and face recognition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations